2020
DOI: 10.1016/j.jcv.2020.104426
|View full text |Cite
|
Sign up to set email alerts
|

Multi-center evaluation of cepheid xpert® xpress SARS-CoV-2 point-of-care test during the SARS-CoV-2 pandemic

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
0
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 8 publications
(9 reference statements)
6
123
0
6
Order By: Relevance
“…Of these, the fastest two (the Abbott ID NOW and the Mesa Accula) with less than 30 min of delay between sampling and answer accumulated evidence of poorer diagnostic performance with a lack of sensitivity [ 5 , 6 ]. Only the Cepheid Xpert Xpress SARS-CoV-2 assay has shown to be a valuable tool with a run-time of 45−50 min with hands on time limited to 2−3 min [ 7 ]. However, due to the pandemic, we are also facing a global shortage of reagents and kits and uncertainty over the availability of Xpert Xpress cartridges [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the fastest two (the Abbott ID NOW and the Mesa Accula) with less than 30 min of delay between sampling and answer accumulated evidence of poorer diagnostic performance with a lack of sensitivity [ 5 , 6 ]. Only the Cepheid Xpert Xpress SARS-CoV-2 assay has shown to be a valuable tool with a run-time of 45−50 min with hands on time limited to 2−3 min [ 7 ]. However, due to the pandemic, we are also facing a global shortage of reagents and kits and uncertainty over the availability of Xpert Xpress cartridges [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Femke et al evaluated Xpert Xpress point-of-care assay (Cepheid GeneXpert systems) for targeting SARS-CoV-2 E-gene and N2-gene in three medical laboratories in the Netherlands. The assay can detect SARS-CoV-2 with a LOD of 8.26 copies/mL in all three laboratories [68]. While Wei et al reported Xpert Xpress test for targeting SARS-CoV-2 E-gene and N2-gene with a LOD of 100 copies/mL [67].…”
Section: Portable Benchtop-sized Analyzersmentioning
confidence: 95%
“…Nucleic acid was extracted and SARS‐CoV‐2 RT‐PCR performed as described above. In addition, samples from inpatients with laboratory‐confirmed COVID‐19 were assessed for SARS‐CoV‐2 by RT‐PCR using the Xpert Xpress SARS‐CoV‐2 assay (Cepheid) according to the manufacturers’ instructions . Semi‐quantitative real time RT‐PCR detection of a human housekeeping gene (RNase P) served as a surrogate marker for the amount of cellular material derived from each swab …”
Section: Methodsmentioning
confidence: 99%